(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
Until the publication of this novel, the works of Zapata that dealt with homosexual themes, beginning with El vampiro de la Colonia Roma (Adonis Garcia, in the English translation) presented a problematic and negative vision of this kind of relationship, as if suggesting that “gay life”, contrary to what the term implies, was a way of life that almost never led to happiness. The novel Melodrama presents an interesting change, proposing a utopian vision of the sexual alternative through the referential use of Mexican filmic melodramas of 40’s and 50’s. In this article, I aim to show how the references to movies, actors and actresses, and even to the boleros that contextualize passional sequences, allow Zapata to deconstruct the stereotypical world of melodrama and, through a story of romance and passion between two men, to reformulate in order to propose that a gay alternative is perfectly possible as a mean to happiness. In the process, he breaks a series of cultural constructions regarding sexuality, including some that originate within the homosexual world itself.